Peran Elektrokardiografi dan Kriteria Peguero–Lo Presti dalam Diagnosis Hipertrofi Ventrikel Kiri - Muhammad Daniyal (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Left ventricular hypertrophy (LVH) can be identified through both electrocardiography (ECG) and echocardiography, with echocardiography recognized as the gold standard for the assessment of LVH. This imaging modality determines the presence of LVH by evaluating the left ventricular mass index (LVMI). For diagnostic purposes, LVH is defined in males as a left ventricular mass index greater than 115 g/m² and in females as greater than 95 g/m². Despite the high accuracy of echocardiography in diagnosing LVH, access to this examination is not universal across all healthcare facilities. Consequently, electrocardiography, a widely available, non-invasive, and cost-effective diagnostic tool, serves as an alternative for the diagnosis of LVH. Several criteria exist for the electrocardiographic assessment of LVH, including the Sokolow-Lyon and Cornell voltage criteria. However, the sensitivity of these electrocardiographic methods remains relatively low, with reported sensitivities of 17% for the Sokolow-Lyon criteria and 35% for the Cornell criteria. In left ventricular hypertrophy, the interstitium experiences changes characterized by fibrosis and other deposits. These alterations can reduce the expression of hypertrophic myocardial tension and limit the diagnostic capabilities of surface electrocardiograms. Additionally, several factors influence electrical tension, including variations in chest wall thickness, heart muscle activity, the distance of the electrode from the left ventricle, and lung activity. The presence of these limiting factors can increase the rate of false negatives in diagnosis. In 2017, Peguero and Lo Presti introduced novel criteria for the diagnosis of LVH, defined by evaluating the deepest S wave and summing it with the S wave in lead V4. According to these new criteria, LVH is identified as ≥ 2.8 mV in men and ≥ 2.3 mV in women. The Peguero-Lo Presti criteria demonstrate improved sensitivity when compared to traditional criteria such as Sokolow-Lyon and Cornell, offering enhanced diagnostic accuracy.